Direction Of The Cost Of Equity Capital In Manufacturing Companies - Irdawati Irdawati; Misnawati Misnawati; Bindarto Bindarto; Yunila Yunila; Hardiyono Hardiyono (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
This study aims to examine the effect of information asymmetry, earnings management, and firm size on the cost of equity capital. This type of research includes causal research using quantitative methods. The population in this study are all manufacturing companies on the Indonesia Stock Exchange. There are 156 manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique in this study was carried out by purposive sampling, so the total sample was 35 data from the financial statements of manufacturing companies. Secondary data was collected through the Indonesian stock exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that information asymmetry had a positive and significant effect on the cost of equity capital; Earnings management has a negative and significant effect on equity capital. At the same time, the company's size has no significant effect on the cost of equity capital.